Kontakt '93 : Skulpturen. - Bex, Florent; Dichter, Claudia; Feidler, Francis; Gentges, Bernd; Hoet, Jan; Kremer, Rudolf; Lambrecht, Luk; Ludwig, Peter; Léonard, René; Pauls, Günther; Schröder, Oswald; Städtische Parkanlagen Klinkeshöfchen Eupen (Eupen : Internationale Kunstzentrum Ostbelgien, 1993)
Bijl, Guillaume ; Charlier, Jacques ; Christiaens, Benoit ; Coeckelberghs, Luc ; Colpaert, Eric ; Corillon, Patrick ; De Bruyckere, Berlinde ; Deleu, Luc ; Gilles, Stéphan ; Janssens, Ann Veronica ; Docte, Philippe Le ; Lizene, Jacques ; Lohaus, Bernd ; Navez, Jean-Marc ; Rombouts, Guy ; Droste, Monika ; Saudoyez, Jean-Claude
Beilage zum GE Nr. 143 vom 23.6.93
Duits
Frans
Nederlands
Kontakt '93 : Skulpturen, Städtische Parkanlagen Klinkeshöfchen Eupen, IKOB (Internationales Kunstzentrum Ostbelgien) Eupen, 26.6. - 10.10.1993
boek
Keywords: België